2021
DOI: 10.1039/d1nj03738b
|View full text |Cite
|
Sign up to set email alerts
|

The in situ fabrication of ZIF-67 on titania-coated magnetic nanoparticles: a new platform for the immobilization of Pd(ii) with enhanced catalytic activity for organic transformations

Abstract: Considering the outstanding characteristics of metal organic frameworks (MOFs) and magnetic nanoparticles, herein, we report a facile approach for the synthesis of magnetic zeolitic imidazolate framework supported palladium(II) catalyst. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sharma et al synthesized Pd@ZIF-67-Fe 3 O 4 -TiO 2 and investigated its catalytic activity on oxidation, reduction and oxidative deprotonation reactions. 31 Further, Qin et al reported the photoreduction of CO 2 using ZIF-67 as a proficient co-catalyst along with ruthenium (Ru) based dye as a photosensitizer. 32 Again, the ZIF-8 catalyst was utilized in the Friedel-Crafts acylation of anisole and benzoyl chloride as reported by Nguyen et al 33 Tran et al reported the effective utilization of ZIF-8 as a heterogeneous catalyst in the Knoevenagel reaction, one of the important reactions of organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al synthesized Pd@ZIF-67-Fe 3 O 4 -TiO 2 and investigated its catalytic activity on oxidation, reduction and oxidative deprotonation reactions. 31 Further, Qin et al reported the photoreduction of CO 2 using ZIF-67 as a proficient co-catalyst along with ruthenium (Ru) based dye as a photosensitizer. 32 Again, the ZIF-8 catalyst was utilized in the Friedel-Crafts acylation of anisole and benzoyl chloride as reported by Nguyen et al 33 Tran et al reported the effective utilization of ZIF-8 as a heterogeneous catalyst in the Knoevenagel reaction, one of the important reactions of organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Paul et al introduced ZIF-67 with palladium ions moieties into amine-functionalized titania-coated magnetic NPs (Fe 3 O 4 -TiO 2 ), the resulting ZIF-67-Fe 3 O 4 -TiO 2 greatly helps in catalytic activity and recyclability in organic transformations. [24] In the present study, we develop a simple and efficient ZnO support-induced in situ encapsulation strategy to fabricate ZnO@Pd/ZIF-8 core-shell catalysts. Ultra-small Pd is uniformly loaded on ZnO@ZIF-8 without agglomeration, indicating that this catalyst can be stably used for a surface reaction.…”
Section: Introductionmentioning
confidence: 99%
“…introduced ZIF‐67 with palladium ions moieties into amine‐functionalized titania‐coated magnetic NPs (Fe 3 O 4 ‐TiO 2 ), the resulting ZIF‐67‐Fe 3 O 4 ‐TiO 2 greatly helps in catalytic activity and recyclability in organic transformations. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, ZIF-67 is a solid block structure with few exposed active sites and high diffusion resistance, which limits its catalytic activity. 28 The researchers propose Ni-Co hollow nanoboxes (Ni-CoHNBs), a nanostructure formed by the evolution of ZIF-67, whose folded surface structure exactly compensates for these defects, providing a huge specific surface area for the sensing platform. [29][30][31] In addition, gold nanoparticles (AuNPs) with good electrical conductivity and biocompatibility are able to bind to Apt through the Au-S bond.…”
Section: Introductionmentioning
confidence: 99%